Comparing Problem-Solving Skills and Cognitive Emotion Regulation in Patients with Psychosomatic Symptoms and Control Population in Isfahan City, Iran - Astara Heidari; Asghar Aghaei; Hamid Afshar (مجله دانشکده پزشکی اصفهان, 2018)
Background: Mental disorders can have physical manifestation and are prevailed as psychosomatic signs. Studies about cognitive skills in psychosomatic patient are clinical trials in order to understand somatotization of mental disorder. This study aimed to compare problem-solving skills and cognitive emotion regulation strategies in patients with psychosomatic symptoms and control population.